2013
DOI: 10.1111/ctr.12241
|View full text |Cite
|
Sign up to set email alerts
|

Rejection after conversion to a proliferation signal inhibitor in chronic heart transplantation

Abstract: We sought to determine the incidence, risk factors, and consequences of acute rejection (AR) after conversion from a calcineurin inhibitor (CNI) to a proliferation signal inhibitor (PSI) in maintenance heart transplantation. Relevant clinical data were retrospectively obtained for 284 long-term heart transplant recipients from nine centers in whom CNIs were replaced with a PSI (sirolimus or everolimus) between October 2001 and March 2009. The rejection rate at one yr was 8.3%, stabilizing to 2% per year therea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Rejections were observed predominantly in the first 6 mo after conversion and to a similar degree in patients with or without CNI treatment. Recently González-Vílchez et al [36] have shown, in 284 longterm HT recipients, a high rate of acute rejection after conversion from a CNI to mTOR-i in maintenance HT. By multivariate analysis, rejection risk was associated with a history of late AR prior to PSI conversion, early Manito N et al .…”
Section: Discussionmentioning
confidence: 99%
“…Rejections were observed predominantly in the first 6 mo after conversion and to a similar degree in patients with or without CNI treatment. Recently González-Vílchez et al [36] have shown, in 284 longterm HT recipients, a high rate of acute rejection after conversion from a CNI to mTOR-i in maintenance HT. By multivariate analysis, rejection risk was associated with a history of late AR prior to PSI conversion, early Manito N et al .…”
Section: Discussionmentioning
confidence: 99%